EFEK TEGANGAN SEARAH (DC) TERHADAP DEWATERING PASTA TOMAT MENGGUNAKAN METODE ELECTROOSMOSIS DEWATERING - Joko Prasetyo; Kamsiatun Eka Pratama; Anang Lastriyanto (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2019)
Tomatoes are fruits that contain a number of important nutrients, such as carbohydrates, vitamin C, vitamin A, vitamin B1, vitamin B2, lycopene, iron, fiber, minerals, and so on. However, tomatoes include climatic fruit, which will rot if not consumed immediately. Under these conditions it’s necessary to process tomatoes into potential products such as tomato paste. Tomato paste production is done by the evaporation process to remove some of the water content. But giving heat to evaporation can damage the nutritional content of the paste. Electroosmosis dewatering is method for reducing water content by placing colloidal suspensions between two electrodes. This method is an interesting to concentrate the suspension that is sensitive to heat. Based on this, research is needed to determine the effect of electroosmosis on reducing water content in tomato paste. In this study, the DC voltage variations used were 0 V, 4.5 V, 9 V, 18 V and 36 V with 100 minutes processing time. The parameters measured based on these variations are changes in DC current during the EOD process and water content of tomato paste. The results showed that DC electric current decreases with increasing processing time, and increases with increasing voltage. the electric current at the lowest voltage variation (4.5 VDC) is 41.40 mA - 59.7 mA, while the electric current at the highest voltage variation (36 VDC) reaches 231.86 mA - 776.67 mA. The increasing DC voltage, the tomato paste water content decreases, so the best stress for the dewatering process is 36 V.